Silica Nanospheres: Hollow Structure Improved Anti‐Cancer Immunity of Mesoporous Silica Nanospheres In Vivo (Small 26/2016). Issue 26 (7th July 2016) - Wang, Xiupeng; Li, Xia; Ito, Atsuo; Yoshiyuki, Kazuko; Sogo, Yu; Watanabe, Yohei; Yamazaki, Atsushi; Ohno, Tadao; Tsuji, Noriko M.
Abstract : Hollow and non‐hollow mesoporous silica nanospheres are synthesized and used for cancer vaccine adjuvants by X. Wang, A. Ito, N. M. Tsuji, and co‐workers on page 3510. The hollow structure of mesoporous silica nanospheres significantly promotes cellular uptake of a model cancer antigen by macrophage‐like cells in vitro, improves anti‐cancer immunity, and increases CD4+ and CD8+ T cell populations in splenocytes of mice in vivo.